Effectiveness of the Community Reintegration Program for Adult Offenders - Aylin Mıhçı; Rukiye Kızıltepe; Türkan Yılmaz Irmak (Psikoloji Çalışmaları)
Offenders experience a number of problems integrating into society after being released from prison. There are examples of many programs that have been developed and implemented in prisons to ensure the reintegration of offenders. The purpose of this study was to examine the effectiveness of the Community Reintegration Program, which was developed for offenders in an open prison. The participants included 60 male offenders between 26 and 44 years of age (M = 36.02, SD = 6.24). The participants were either assigned to an education group (N = 30) or comparison group (N = 30). To evaluate the effectiveness of the education program, the participants completed the Anger Expression and Trait Anger Scale, Perceived Stress Scale, Communication Skills Scale, and Personal Information Form before and after the intervention. The education group participated in a six-week Community Reintegration Program, which comprised three sessions that included communication skills and coping with stress and anger. A series of 2 X 2 repeated measures ANOVA and ANCOVA analyses were conducted to investigate the program’s effectiveness. The findings revealed that the interaction effects between group and time were significant for the scores of the subscales of the Communication Skills Scale, specifically, basic skills and personal/self-expression, caring communication, willingness to communicate, active listening and non-verbal communication, and complying with communication principles as well as the three subscales of the Anger Expression and Trait Anger Scale, namely, anger-in, anger-out, and anger control. In relation to communication skills and anger management, the program was found to be effective among those in the education group. However, with regard to trait anger, insufficient self-efficacy, and perceived stress/distress, the program was ineffective. Despite its limitations, this study contributed significantly to the literature on intervention programs for adult offenders. It is recommended that the effectiveness of the program be explored in various institutions. It is further suggested that anger and stress should be measured after the program is improved